PENGARUH REGULASI DAN KAPABILITAS PERUSAHAAN DALAM MENINGKATKAN KINERJA BISNIS AGEN GAS LPG 3KG DI KOTA MAKASSAR - Kiki Resky Ramdhani Sucipto; Anhar Januar Malik (Pusat Riset dan Inovasi Nasional, 2021)
The purpose of this research to know the role of regulation, increasing the company’s capabilities to enhance the business performance of agencies LPG 3kg in the city of Makassar South Sulawesi. The research method used is descriptive method and verification. A source of data in this study us the primary and secondary data. The primary data is using the questionnaire census technique, and the are 40 respondents. Verification analysis in this research using the Partial Least Square (PLS) method with Smart PLS 2.0 software. The result of the research on the influence of regulation, and the company’s capabilities in improving business performance LPG gas Agent 3 kg, where the influence of regulation and corporate capability against influential business performance may of 0,911. The influence of regulation on government regulation of the most influential and dominant in the regulatory of the government and Pertamina with and average yield of 3,74 and the on the variables of common capabilities the most dominant dimensions is on human resource their influence to business performance. On a good company performance, the agents should follow applicable regulations and drafting capabilities the company appropriately and does comply the regulations from government and Pertamina, so that the company can grow especially performance expected in the financial perspective the company the lowest compared to other dimensions that exist on this variable.